Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So the problem is as follows:

Prove that if H is a subgroup of G, then H is a normal subgroup of G iff the following condition holds: $$\forall x,y \in G, xy \in H \iff yx \in H$$

It's all completed now:

We are given that H is a subgroup of G.

($\def\impl{\;\Rightarrow\;}\impl$) Assume H is a normal subgroup of G. So, $$\forall h \in H, \forall g \in G, ghg^-1 \in H.$$ Suppose $$\forall x,y \in G, xy \in H.$$ Since H is a normal subgroup of G and $$y \in G,$$ we know $$y(xy)y^-1\in H \impl yx(yy^-1)\in H \impl yxe \in H \impl yx \in H.$$ Similarly, suppose $$\forall x,y \in G, yx \in H.$$ Since H is a normal subgroup of G and $$x \in G,$$ we know $$x(yx)x^-1\in H\impl xy(xx^-1)\in H\impl xye \in H\impl xy \in H.$$

($\;\Leftarrow\;$) Assume $$\forall x,y\in G, xy\in H \iff yx \in H.$$ Now let $$a=yx \impl xa=x(yx) \impl (xa)x^-1=(xy)xx^-1 \impl xax^-1 = xy.$$ So $$ \forall x\in G, \forall a\in H, a \in H \impl xax^-1 \in H.$$ Therefore H is a normal subgroup of G.

share|improve this question
    
For third and fourth check you do is a symmetric condition so you don't need to worry about the "iff" –  muzzlator Mar 19 '13 at 8:03
add comment

1 Answer

Note first that the elements $xy$ and $yx$ are conjugate, as $$ x^{-1} (xy) x = y x. $$ Conversely, if $a$ and $b$ are conjugate, $b = z^{-1} a z$, say, then $$ b = (z^{-1} a) z, \quad a = z (z^{-1} a) $$ so $a = xy$ and $b = yx$, for $x = z$ and $y = z^{-1} a$.

Now use the definition of normal subgroup.

share|improve this answer
    
Which direction is this for? –  Katie Mar 19 '13 at 9:48
    
@Katie, both directions. It shows that your statement is equivalent to the definition. –  Andreas Caranti Mar 19 '13 at 9:54
    
Sorry, I'm having a hard time seeing how it implies anything. Using a similar idea, I was able to prove this in the forward direction, but I'm still stuck using this fact to prove it in reverse. Also, the definition of normal subgroup says that $$\forall h\in H, \forall g\in G, ghg^-1\in H.$$ This is distinct from if it were to say $$g^-1hg\in H$$ because we are not given that it is abelian. –  Katie Mar 19 '13 at 10:01
    
@Katie, your assumption is $xy \in H$ implies $yx \in H$ for all $x, y \in G$. Write $a = xy$, and then $yx = x^{-1} a x$. So your assumption now reads $a \in H$ implies $x^{-1} a x \in H$ for all $a \in H$ and $x \in G$. This is exactly the definition of a normal subgroup $H$. –  Andreas Caranti Mar 19 '13 at 10:24
    
Now I see what you're saying, thank you! –  Katie Mar 19 '13 at 10:32
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.